Board Governance Attributes and Organizational Characteristics of Mosque Co-Operatives in Malaysia - Sallehhuddin, Abdullah; Shamsudin, Azizi; Abu Said, Al Mansor; Jais, Mohammad; Ariff Mustafa, Mohd; Shukor Masuod, Md; Hasmanto, Nor; Ismail, Hishamuddin (International Journal of Engineering and Technology, 2018)
Performances of mosque co-operatives rely on the effectiveness of the board of governance. The board has responsibilities to determine the strategic direction of mosque co-operatives, oversight management, and ensure the integrity of membersâ€™ rights and interests. The board of governance functions is becoming more challenging since the launching of National Co-operative Policy II (2011-2020), which among another, place greater emphasis on the expansion of mosque co-operatives movement via initiative of 1 Community, 1 Co-operative. Furthermore, the board of governance of mosque co-operatives is expected to deliver not only economic performance but also socio-economic governance, especially in supporting the activism of mosque institutions. Hence, as an initial observation, this study attempts to highlight the board governance attributes and mosque co-operatives organisational characteristics. The initial findings are essential in assisting regulator and policy maker like Ministry of Domestic Trade, Co-operative, and Consumerism (KPDNKK), Malaysia Co-operative Societies Commission (SKM), and Malaysia National Co-operative Movement (ANGKASA) in preparing the Mosque Co-operative Strategic Plan 2017-2020, and National Co-operative Policy III (2021-2030).Â Â